Pocket Fowler's modern English usage - Allen, R. E; Oxford University Press (New York ; Oxford : Oxford University Press, 2008)
Searchable database of information found in the Pocket Fowler's modern English usage. This edition is based on the work of Robert W. Burchfield's New Fowler's modern English usage
Title from title screen
Text and search engine
Mode of access: World Wide Web
Keywords: English language -- Usage -- Dictionaries; Electronic books